The Role of Quantitative Aortographic Assessment of Aortic Regurgitation by Videodensitometry in the Guidance of Transcatheter Aortic Valve Implantation - Miyazaki,Yosuke (2018)
Abstract Background: Balloon post-dilatation (BPD) is often needed for optimizing transcatheter heart valve (THV) implantation, since paravalvular leak (PVL) after transcatheter aortic valve implantation is associated with poor outcome and mortality. Quantitative assessment of PVL severity before and after BPD is mandatory to properly assess PVL, thus improving implantation results and outcomes. Objective: To investigate a quantitative angiographic assessment of aortic regurgitation (AR) by videodensitometry before and after BPD. Methods: Videodensitometric-AR assessments (VD-AR) before and after BPD were analysed in 61 cases. Results: VD-AR decreased significantly from 24.0[18.0-30.5]% to 12.0[5.5-19.0]% (p < 0.001, a two-tailed p < 0.05 defined the statistical significance). The relative delta of VD-AR after BPD ranged from -100% (improvement) to +40% (deterioration) and its median value was -46.2%. The frequency of improvement, no change, and deterioration were 70% (n = 43), 25% (n = 15) and 5% (n = 3), respectively. Significant AR (VD-AR > 17%) was observed in 47 patients (77%) before and in 19 patients (31%) after BPD. Conclusions: VD-AR after THV implantation provides a quantitative assessment of post-TAVI regurgitation and can help in the decision-making process on performing BPD and in determining its efficacy.